2017
DOI: 10.11606/rdg.v33i0.125767
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças nos Padrões da Temperatura do Estado de São Paulo/Brasil nos Últimos 50 Anos

Abstract: Resumo: Um dos temas mais relevantes discutidos atualmente é a questão da variabilidade e das mudanças climáticas. Diversas pesquisas apontam que as temperaturas mundiais têm aumentado consubstancialmente, nos últimos anos, e, especialmente devido a fatores como o uso e ocupação do solo e diferentes formas de poluição. Embasados nesta discussão o objetivo deste artigo é apresentar alguns dados oriundos desta relação sociedadenatureza tomando como viés analítico a variabilidade e aumento das temperaturas, em qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…However, some hypotheses for these pattern changes include the degree of susceptibility of populations in different Brazilian regions 58 , 61 and climate change associated with greenhouse gas emissions 62 . For example, the highest temperature increase in the state of São Paulo over the last few decades was observed in municipalities located on the São Paulo coast 63 .…”
Section: Discussionmentioning
confidence: 99%
“…However, some hypotheses for these pattern changes include the degree of susceptibility of populations in different Brazilian regions 58 , 61 and climate change associated with greenhouse gas emissions 62 . For example, the highest temperature increase in the state of São Paulo over the last few decades was observed in municipalities located on the São Paulo coast 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The thermal response of urban materials present on the surface (urban targets captured by remote sensing, mostly characterized by watertight and little evaporative materials) shows lower thermal capacity for these components, which require less energy to heat up in the presence of radiation. However, urban surface components do not conserve energy after sunset, providing heat to the adjacent atmosphere that becomes warmer than the surfaces [22,46].…”
Section: Discussionmentioning
confidence: 99%
“…Among the variables in the analysis, the highest rise was observed in the Tmin, with values of 1.5 °C above the historical average (Figure 2b). Fante and Sant'Anna Neto (2017) analyzing changes in the air temperature patterns into the São Paulo state, found that raises in the minimum air temperature was more prominent compared with maximum air temperature. A considerable increase in the air temperature also was observed during 2014 and 2015.…”
Section: Annual Data Variabilitymentioning
confidence: 99%